U.S. justifications for the use of force in Syria through the prism of the Responsibility to Protect. (3rd July 2021) - Ross, Simona
ABSTRACT: The scale and gravity of the Syrian conflict has led to calls for the international community to fulfil its responsibility to protect the people. Despite mounting evidence of atrocity crimes committed by the Syrian government and ISIL, the U.S. administrations' legal justifications for the use of force have centred on more established – albeit in the Syrian context controversial – legal justifications, illustrating the limitations of the Responsibility to Protect in providing a legal framework for the use of force on humanitarian grounds. Nonetheless, the Syrian crisis represents a critical juncture in the evolution of the Responsibility to Protect and the legal justifications provided by the U.S. have implications on this development, particularly with regards to the doctrine's third pillar on the use of force.